Chain dimensions and dynamic dilution in branched polymers. (25th July 2016) - Yan, Zhi-Chao; Vlassopoulos, Dimitris
Abstract: We revisit old ideas for classifying branched polymers based on their size or intrinsic viscosity relative to that of respective linear chains and complement them with an analysis of their dynamics, which is based on the concepts of hierarchical relaxation and dynamic dilution. By using several old and new datasets from different well-defined polymer architectures such as combs, H-polymers, and stars, we quantify the role of diluted entanglements on the viscoelastic properties. We suggest that the combination of static and dynamic data on sizes and relaxation mechanisms (and in particular accounting for dynamic dilution), respectively, provides a complete quantitative characterization of branched polymers over a wide range of architectures. The combined generic phenomenological description based on specific scaling parameters (branching number, backbone fraction, diluted number of entanglements, packing length) may provide useful information about complex polymers without resorting to detailed molecular modeling and moreover, allow designing or selecting specific macromolecular systems with desired properties. Graphical abstract: Left: The size ratio g as function of backbone fraction and branching number f in a three-dimensional plot. Different macromolecular structures are illustrated by cartoons. The grids presents predictions based on Casassa's model. Right: Backbone plateau modulus as function of reduced packing fraction for diluted backbone of comb architectures. Highlights: Analysis of viscoelastic properties (moduli, relaxation times) of entangled branched polymers based on dynamic dilution. Master plots of recoverable compliance and backbone-to-arm time ratios versus diluted number of backbone entanglements. Generalized representation of the dependence of entanglement plateau modulus on packing length. Dilute solution and entangled polymer properties behave universally as functions of molecular and branching characteristics. Universality of scaling parameters (branching number, backbone fraction, diluted number of entanglements, packing length).